1997
DOI: 10.1128/jb.179.14.4464-4472.1997
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the alginate biosynthetic gene cluster in Pseudomonas syringae pv. syringae

Abstract: Alginate, a copolymer of D-mannuronic acid and L-guluronic acid, is produced by a variety of pseudomonads, including Pseudomonas syringae. Alginate biosynthesis has been most extensively studied in P. aeruginosa, and a number of structural and regulatory genes from this species have been cloned and characterized. In the present study, an alginate-defective (Alg ؊ ) mutant of P. syringae pv. syringae FF5 was shown to contain a Tn5 insertion in algL, a gene encoding alginate lyase. A cosmid clone designated pSK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
84
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 60 publications
11
84
0
2
Order By: Relevance
“…Among plant pathogenic pseudomonads, alginate production has been linked to epiphytic fitness and the production of watersoaked lesions (53). All of the genes required for alginate biosynthesis in P. aeruginosa are present in DC3000, although some of the alginate regulatory genes are absent, indicating that the regulation of alginate biosynthesis differs between P. aeruginosa and P. syringae, consistent with previous reports (54). Three genes encoding levansucrases, required for the biosynthesis of the polysaccharide levan, were also identified in DC3000.…”
Section: Ttss and Effectorssupporting
confidence: 80%
“…Among plant pathogenic pseudomonads, alginate production has been linked to epiphytic fitness and the production of watersoaked lesions (53). All of the genes required for alginate biosynthesis in P. aeruginosa are present in DC3000, although some of the alginate regulatory genes are absent, indicating that the regulation of alginate biosynthesis differs between P. aeruginosa and P. syringae, consistent with previous reports (54). Three genes encoding levansucrases, required for the biosynthesis of the polysaccharide levan, were also identified in DC3000.…”
Section: Ttss and Effectorssupporting
confidence: 80%
“…g. Strain did not elicit tissue collapse (an HR) when inoculated into tobacco leaves at 5 ¥ 10 genes known to be involved in P. syringae pathogenesis. These include hrp/hrc genes (Galan and Collmer, 1999), genes encoding putative effectors of the hrp/hrc type III secretion system located both within the conserved effector locus (CEL) flanking the hrp/hrc cluster (Alfano et al, 2000) and elsewhere in the genome (virPphA, avrPpiB and avrPphD; Cournoyer et al, 1995;Jackson et al, 1999;Arnold et al, 2001a), biosynthetic genes for the P. syringae phytotoxin coronatine (cfl, cfa; Bender et al, 1999) and algA, which directs the synthesis of the exopolysaccharide alginate (Peñaloza-Vázquez et al, 1997). Additionally, several ipx fusions are to novel genes that would be predicted to be involved in virulence, including a gene encoding a putative pectin lyase (ipx31), which may be involved in degrading plant cell walls.…”
Section: Ipx Genes Known or Predicted To Be Involved In Virulencementioning
confidence: 99%
“…In Azotobacter vinelandii, which expresses extracellular epimerases, this mechanism controls the degree of epimerization (11,14). In bacteria a periplasmic ME is encoded by algG, which is found in the alginate biosynthetic gene cluster (15)(16)(17). Previous studies demonstrated that epimerase-defective algG mutants of Pseudomonas aeruginosa or Pseudomonas fluorescens produce pure polymannuronic acid, which suggests that algG is the sole ME in these bacteria (15,18).…”
mentioning
confidence: 99%